Pendekatan Program Mother Smart Grounding (MSG) dalam Pencegahan Stunting pada Anak dan Modifikasi Makanan Sehat - Mila Triana Sari; Miko Eka Putri; Melda Amalia; Daryanto Daryanto; Fithriyani Fithriyani; Tuti Alawiyah (Jurnal Abdimas Kesehatan (JAK), 2023)
The stunting rate in Indonesia is 21.6%. This figure is based on the results of the 2022 Indonesian Nutrition Status Survey (SSGI), the stunting rate decreased by 2.8% from 2021, while the government's target for 2024 is that the stunting rate in Indonesia is 14%, for this reason the government has made various efforts to meet the target. 2024. Based on data from the Jambi Provincial Health Service in 2018, for Jambi Province, the stunting prevalence rate was 30.1% with the highest percentage of stunting found in West Tanjung Jabung Regency (44%) and the lowest in Sarolangun Regency 18.8%, for Jambi City the figure Stunting incidence 26.2%. Catfish has important nutritional benefits in preventing stunting in toddlers. Apart from catfish containing high nutritional value, catfish is a type of fish that is easy to find and cheap. So the consumption of catfish is an effort to overcome stunting in toddlers that can be reached by both upper and lower classes of society. Apart from that, in efforts to overcome stunting, the community needs to be given an understanding of the importance of nutrition for toddlers and early childhood, namely by providing education to mothers of toddlers and early childhood with the Mother Smart Grounding (MSG) program at Mukti Tama Kindergarten, Jambi City, targeting mothers. Teachers of Mukti Tama Kindergarten students. Activities are carried out by: Lectures, Visual Presentations, group discussions. Results: an increase in the average knowledge of mothers and parents of Mukti Tama KB Kindergarten children with an average of 2.0. Conclusion: Most of the participants, 85%, responded very well to the material provided. There needs to be continuous health education activities in coordination between kindergartens and health workers holding the KIA program in the PKM Simpang Kawat work area.